Phytohormone effect on Pterocephalus depressus stock plant productivity and phytohormone accumulation and movement - Markovic, Sean, author; Klett, Jim, advisor; Newman, Steven, committee member; Pilon-Smits, Elizabeth, committee member; Prenni, Jessica, committee member; Argueso, Cris, committee member (Colorado State University. Libraries, 2021)
Moroccan pincushion (Pterocephalus depressus) is a drought tolerant perennial that is being used in landscapes throughout arid areas of the western United States. Commercial producers have had difficulty in producing enough plants to meet demand for moroccan pincushion due to production and propagation stock plant problems. Producers of comparable ornamental perennials have increased their use of gibberellic acid 3 (GA3) in stock plant production. The use of GA3 has increased the yield of vegetative cuttings from perennial stock plants. The plant hormone GA3 is involved in many physiological processes, including plant growth and development. In current literature, few reports are available on the interaction between exogenous GA3 and other plant hormones and their effect on successful propagation of vegetative cuttings. However, the research clearly demonstrated that several different hormone interactions with GA3 could beneficially affect the cutting's rooting physiological process. First, this study describes two experiments researching optimization of stock plant production. Moroccan pincushion stock plants received foliar applications of GA3, benzyladenine, ethephon, or indole-3-butyric acid (IBA) plant growth regulators (PGR). Plant growth regulators were applied singularly and in combination with GA3 to determine efficacy on stock plant production. A propagation study was conducted simultaneously to determine effects of these different PGR treatments on the rooting of moroccan pincushion cuttings. The stock plant study showed GA3 + benzyladenine increased cutting production over other treatments. Fresh weight of moroccan pincushion did not differ among treatments. While dry weight showed no differences in experiment 1, but in experiment 2 differences were observed. The GA3 + IBA treatment had the greatest overall growth. Treatments that included GA3 were all greater in average growth index [(height + width + width)/3] and differed from those without GA3 being applied. The propagation experiments indicated rooting percentages did not differ among treatments. However, growers look for 100% rooting and GA3 + IBA was the only treatment with 100% rooting percentage for both experiments indicating potential benefits. The second part of this paper was to determine the movement and accumulation of GA3 and IBA in treated moroccan pincushion (Pterocephalus depressus). Plants were treated with GA3 alone and in combination with benzyladenine, ethephon, or IBA by either a foliar or drench application method. The amount of GA3 and IBA found in basal and apical sections of moroccan pincushion was analyzed using liquid chromatography/ mass spectrometry (LC/MS). Results shown that drench applications effected the movement of GA3 when GA3 was combined with IBA or benzyladenine. The movement of IBA was affected by drench applications the greatest when GA3 + IBA were applied. Both GA3 and IBA were found in the greatest abundance when plants were treated with GA3 + IBA in apical areas of moroccan pincushion. Nutrients in the cuttings were also analyzed. Only potassium had a significant difference for the amount found when treated with GA3 as a drench application. Other nutrients detailed in this study were not affected by different PGR treatments. This study highlights the beneficial effect of GA3 on production of vegetative cuttings without adverse effects on successful rooting of the cutting.